Integration of Formal Proof into Unified Assurance Cases - With Isabelle/SACM. (16th August 2021) - Foster, Simon; Nemouchi, Yakoub; Gleirscher, Mario; Wei, Ran; Kelly, Tim
Abstract: The paper, by Simon Foster, Yakoub Nemouchi, Mario Gleirscher, Ran Wei and Tim Kelly, published in The Formal Aspects of Computing—Applicable Formal Methods (June 2021), explores the introduction of Isabelle/SACM into formal methods of assurance.